"Fantastyka" (bibliografia zawartości) = "Fantasy" ["Fantastyka"] (the content's bibliography) - Radzijewska, Wioletta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The magazine "Fantasy" was published in the years of 1982-1990, in 1990 it was renamed into "New Fantasy" ["Nowa Fantastyka"] and became a continuation of the original one. "Fantasy" seems to be the most popular Polish monthly periodical dedicated to fantasy and science fiction literature. It was the first journal concentrating on such themes in Poland, and even in the whole eastern Europe, therefore it gained fans very quickly after its debut. The first editor in chief was Adam Hollanek, now ? Jakub Winiarski.
Keywords: "Fantastyka"; czasopismo polskie; fantastyka; bibliografia; fantasy; bibliography